Research-development partnerships for scaling complex innovation: Lessons from the Farmer Business School in IFAD-supported loan-grant collaborations in Asia - Prain, Gordon; Wheatly, C.; Odsey, C.; Verzola, L.; Bertuso, A.; Roa, J.; Naziri, D. (Elsevier, 2020)
The Farmer Business School (FBS) is a participatory, action learning process focused on product and business development, and like the Farmer Field School, is a complex, multi-dimensional innovation with the potential to benefit large numbers of farming households economically, socially and institutionally. Scaling this approach requires rethinking both innovation and scaling. The paper draws on the insights of recent research which argues that a systems approach to innovation can better address the complexity of scaling processes and provides frameworks that link together processes of innovation and scaling. In examining these frameworks, the paper identifies the key role of partnership dynamics in those processes. Drawing on both the innovation and scaling literature and literature on partnership dynamics, a conceptual framework is developed to analyze how partnership dynamics contribute to and constrain the transition from small-scale ‘niche’ innovation testing led by researchers, to large scale integration of the approach by development partners in agricultural ‘regimes’. Using case studies involving partnerships between a small international agricultural research grant recipient and six large development projects supported by IFAD multilateral loans and managed by government agencies undertaken in four Asian countries between 2011 and 2018, the study analyses the variable dynamics of the partnerships from initial networking to integrated collaboration, in the process of scaling the FBS innovation. Responding to the main research question about the drivers of partnership dynamics that contribute to scaling, the paper examines the partnerships in terms of six drivers which derived both from the literature and also from the empirical evidence presented in the study. The drivers include two dimensions of “fit”, one about the convergence of research expertise and development demand, the other about the systematic integration of the innovation with different elements of the development actions. Other drivers relate to the issue of the convergence of project cycles, the stability of staffing in partner organizations, internal decision-making processes and the dimension of “partnering” – the value-based and behavioral aspects of collaboration. The paper also discusses the results of a “partnership health check-up” process conducted periodically during the partnerships and reconsiders the driver about system fit to understand the extent to which there had been a transformation in the conventional ‘regime’ approach to innovations and scaling. Finally, the paper proposes to adjust the conceptual framework based on the analysis of these partnerships for scaling innovations.